Methylglyoxal (MGO) in Italian Honey - Valentina Terio; Giancarlo Bozzo; Edmondo Ceci; Alessandra Emilia Savarino; Roberta Barrasso; Angela Di Pinto; Anna Mottola; Patrizia Marchetti; Giuseppina Tantillo; Elisabetta Bonerba (Applied Sciences, 2021)
Methylglyoxal (MGO) is recognized as being the bioactive component responsible for the antibacterial activity of mānuka honey. MGO content was investigated by high-performance liquid chromatography (HPLC-UV), in isocratic elution, to assess the occurrence of this compound in mono- and multi-floral honey samples representative of different botanical and geographic origins in Italy. Specifically, 110 honey samples from sweet cherry tree (Prunus avium L.), thyme (Thymus vulgaris L.), almond tree (Prunus amygdalus L.), eucalyptus (Eucalyptus camaldulensis L.), coriander (Coriandrum sativum L.), cornflower (Centaurea cyanus L.), thistle (Silybum marianum L.), acacia (Robinia pseudoacacia L.), citrus, honeydew and multifloral honey were considered. The amount of MGO found in different types of honey was ranging from 0.4 to 24.1 mg/kg. This study provides, for the first time, data on MGO levels in Italian cherry and almond honey, which showed higher concentrations of MGO compared to honeys from other botanical species.